THE EFFECT OF WORK ENVIRONMENT, MOTIVATION, AND WORK EXPERIENCE ON EMPLOYEE PRODUCTIVITY OF KUD PAMA IMU ENDE - Kurniawan, Ignatius Soni; Rimas, Maria Elviana (Jurnal Ekonomi Balance, 2021)
This research was conducted to determine the effect of work environment, motivation, and work experience on employee productivity. The population in this study were all employees of the Koperasi Unit Desa Pama Imu, Kabupaten Ende, Nusa Tenggara Timur. Samples were taken as many as 50 respondents using saturated sampling technique. Data were collected using a questionnaire and tested using multiple linear regression analysis. The results of this study indicate that the work environment and work experience have no effect on employee productivity. Motivation has a positive effect on employee productivity. Organizational leaders are expected to increase work motivation items to increase employee productivity.